Implicit Differentiation examples with detailed solutions are presented
Example 1: Use implicit differentiation to find the derivative dy / dx where y x + sin y = 1
Solution to Example 1:
Use the sum rule of differentiation to the whole term on the left of the given equation.
d [xy] / dx + d [siny] / dx = d/dx .
Differentiate each term above using product rule to d [xy] / dx and the cain rule to d [siny] / dx.
x dy / dx + y + (dy / dx) cos(y) = 0 .
Note that in calculating d [siny] / dx, we used the chain rule since y is itself a function of x and sin (y) is a function of a function.
Solve for dy/dx to obtain.
dy / dx = -y / (x + cos y)
Example 2: Use implicit differentiation to find the derivative dy / dx where y 4 + x y 2 + x = 3
Solution to Example 2:
Use the differentiation of a sum formula to left side of the given equation.
d[y 4] / dx + d[x y 2] / dx + d[x] / dx = d / dx
Differentiate each term above using power rule, product rule and chain rule.
4y 3 dy / dx + (1) y 2 + x 2y dy / dx + 1 = 0
Solve for dy/dx.
dy/dx = (-1 - y 2) / (4y 3 + 2xy)
Example 3: Find all points on the graph of the equation
x 2 + y 2 = 4
where the tangent lines are parallel to the line x + y = 2
Solution to Example 3:
Exercises Use implicit differentiation to find dy/dx for each equation given below.
Rewrite the given line x + y = 2 in slope intercept form: y = -x + 2 and identify the slope as m = -1. The tangent lines are parallel to this line and therefore their slope are equal to -1. The slope of tangent lines at a point can be found by implicity differentiation of x 2 + y 2 = 4
2x + 2y dy/dx = 0
Let P(a , b) be the point of tangency. At point P the slope is -1. Substituting x by a, y by b and dy/dx by -1 in the above equation, we obtain
2a + 2b (-1) = 0
Point P(a , b) is on the graph of x 2 + y 2 = 4, hence
a 2 + b 2 = 4
Solve the system of equations: 2a - 2b = 0 and a 2 + b 2 = 4 to obtain two points
(-sqrt(2) , -sqrt(2)) and (sqrt(2) , sqrt(2))
1: xe y = 3
2: x 2 + y 2 = 20
3: x sin(xy) = x
solutions to the above exercises
1: dy/dx = - 1 / x
2: dy/dx = - x / y
3: dy/dx = [ 1 - sin(xy) -xy cos(xy) ] / [ x2 cos(xy)]
More on differentiation and derivatives